Visualising the lubrication condition in hydrodynamic journal bearings using impedance measurement - Koetz, Florian; Schmitt, Florian; Kirchner, Eckhard; Zancul, Eduardo (Frontiers in Mechanical Engineering, 2024)
IntroductionThe demand to increase reliability and reduce maintenance costs drives the search for new condition monitoring solutions of machines. Bearings are of special interest in this matter as they are main contributors to machine downtime. Therefore, this article investigates the electric behavior of a hydrodynamic journal bearing using impedance measurement.MethodsFor that purpose measurements are taken in boundary lubrication, mixed lubrication and hydrodynamic lubrication of a hydrodynamic journal bearing. In order to interpret the behaviour observed in these measurements, a phenomenological model is developed using the quantitative working space model. The measurement results are also interpreted using analogies to the Stribeck curve as a known tribological model. Additionally, measurements in mixed lubrication are analysed in detail.ResultsThese measurements show that the electric behaviour of journal bearings changes significantly within the mixed lubrication regime. This change in behaviour shows three distinct states within mixed lubrication which helps to identify destructive operating conditions. Furthermore, the measurements potentially allow the detection of deformation or damage of the bearing in mixed lubrication.DiscussionThe quantitative analysis of the electric behaviour of journal bearings is possible in the mixed lubrication regime and can be used in future to extract condition and operating information from a system during operation.